2017
DOI: 10.1007/s00586-017-5060-4
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive nerve stimulation as a diagnostic aid for distinguishing cervical spondylotic amyotrophy from amyotrophic lateral sclerosis

Abstract: The application of RNS, especially in proximal muscles, may provide a simple accurate and noninvasive supplementary test for distinguishing CSA from ALS, even in the early stage of these diseases. A combination of RNS, needle EMG, clinical features and cervical magnetic resonance imaging may yield sufficient diagnostic information to differentiate CSA and ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
2
20
1
Order By: Relevance
“…The patients in the positive decrement group had lower ALSFRS-R scores compared with those in the decremental negative group, suggesting that the former were worse. Some studies have shown that the disease progressed more rapidly in ALS patients with a positive decrement (4,8,13,14), but others contradicted this (5,7,(15)(16)(17). If the RNS decrement responses were not related to the disease progression, the interpretation of the mechanism of decrement responses, the early neural reinnervation, may need to be corrected (5).…”
Section: Discussionmentioning
confidence: 99%
“…The patients in the positive decrement group had lower ALSFRS-R scores compared with those in the decremental negative group, suggesting that the former were worse. Some studies have shown that the disease progressed more rapidly in ALS patients with a positive decrement (4,8,13,14), but others contradicted this (5,7,(15)(16)(17). If the RNS decrement responses were not related to the disease progression, the interpretation of the mechanism of decrement responses, the early neural reinnervation, may need to be corrected (5).…”
Section: Discussionmentioning
confidence: 99%
“…We divide the ALS patients into RNS positive (RNS+) and RNS negative (RNS-) group by whether percentage decrease of Del or Trap is greater or less than -10% [13]. The diagnostic delay time is statistically shorter and ALS- FRS-r score is statistically lower in RNS+ group than RNS-group (p = 0.002, 0.000).…”
Section: Resultsmentioning
confidence: 99%
“…So we only conducted slow-rate RNS in axillary and accessory nerves. A decremental response exceeding 10% was considered abnormal in this study according to the conventional criterion suggested by the AAEM Quality Assurance Committee [13].…”
Section: Methodsmentioning
confidence: 99%
“…However, the pathological mechanism and the clinical implications of this phenomenon remain elusive. [ 4 5 6 7 8 9 10 ] Immature sprout, due to denervation and innervation after MN loss, is typically considered a possible mechanism. The animal experiments demonstrated the possibility of NMJs defection occurring before any loss of MNs, termed the “dying back” theory.…”
Section: Introductionmentioning
confidence: 99%